Tear gas epiphanies : protest, culture, museums - Robertson, Kirsty, 1976- (McGill-Queen's/Beaverbrook Canadian Foundation studies in art history., 2019)
"Museums are frequently sites of struggle and negotiation. They are key cultural institutions that occupy an oftentimes uncomfortable place at the crossroads of the arts, culture, various levels of government, corporate ventures, and the public. Because of this, museums are be targeted by political action but can also provide support for contentious politics. Though protests at museums are understudied, they are far from anomalous. Tear Gas Epiphanies traces the as-yet-untold story of political action at museums in Canada from the early twentieth century to the present. The book looks at how museums do or do not archive protest ephemera, examining a range of responses to actions taking place at their thresholds, from active encouragement to belligerent dismissal. Drawing together extensive primary-source research and analysis, Robertson questions widespread perceptions of museums, strongly arguing for a reconsideration of their role in contemporary society that takes into account political conflict and protest as key ingredients in museum life. The sheer number of protest actions Robertson uncovers is compelling. Ambitious and wide-ranging, Tear Gas Epiphanies provides a thorough and conscientious survey of key points of intersection between museums and protest--a valuable resource for university students and scholars, as well as arts professionals working at and with museums."--